Hubungan Pola Asuh Orang Tua Terhadap Perkembangan Sosial Anak Di Tk Aisyiyah Gonilan Kartasura Sukoharjo Tahun Ajaran 2015/2016 - Saputri, Cindy Ratna; , Dra. Surtikanti, SH, M.Pd; , Dra. Surtikanti, SH, M.Pd (2016)
The purpose of this research is to know the relathionship between parenting parents towards the child's social growth. The research design was descriptive correlational. The sample was 59 child's in B class using Sample Random Samplin technique. Collection technique used questionnaire. This research use product moment correlations for the analysis method. It meant that the research had a positive correlation and this correlation was significant. Based the results of the analysis of the data obtained the result was that there was a relationship between parenting parents toward the child's social growth in Aisyiyah Gonilan Kartasura Sukoharjo Kindergarten Academic Year 2015/2016. This was proved by the results of r pearson- correlation -0.465 with significance of 0.000 < 0.01 (p = 0.000; p < 0.01) it meant that it had denied ho's relationship between parenting parents were permissive with children social growth in Aisyiyah Gonilan Kartasura Sukoharjo Kindergarten Academic Year 2015/2016.